DESAIN DAN ANALISIS SPECIAL TOOL POWER SECTION PT6-42 MENGGUNAKAN METODE ELEMEN HINGGA - Wira Gauthama; Ready Kresna Nanda Suprapto (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2022)
The goal of this research is to use the finite element method to develop and analyze a frame for supporting the PT6-42 power section. The software SolidWorks 2020 was used to do the static analysis. ASTM 500 and ASTM A36 were utilized for the frame. The load used is 95 kg, which is the power section's burden. The results of the analysis show the design. The safety factor values obtained by using ASTM A36 and ASTM A500 materials on special tools with a thickness of 10 mm are 2.06 and 2.60, respectively. Frame with a size of 5 mm is not recommended because they are only safe to withstand static loads.